2013
DOI: 10.2147/ijnrd.s44656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hepatitis C virus infection on erythropoiesis in patients on hemodialysis

Abstract: Background: Erythropoietin is a hormone that regulates erythropoiesis and is mainly produced by the kidneys. Several animal studies as well as a few case reports and case series have demonstrated that regenerating hepatic tissue can produce more erythropoietin than normal hepatic tissue. The purpose of the study was to examine the difference in hemoglobin and hematocrit levels as well as epoetin dosage in patients on hemodialysis with and without hepatitis C (HCV). Methods: A retrospective chart review was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
3
1
0
1
Order By: Relevance
“…ERI values of anti-HCV-positive patients were lower than those of anti-HCV-negative ones; however, the difference wasn't statistically significant. This is in agreement with a recent study [52] which found that average required dose of Epo was lower in the anti-HCV-positive group than in the anti-HCVnegative group.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 93%
“…ERI values of anti-HCV-positive patients were lower than those of anti-HCV-negative ones; however, the difference wasn't statistically significant. This is in agreement with a recent study [52] which found that average required dose of Epo was lower in the anti-HCV-positive group than in the anti-HCVnegative group.…”
Section: Individual Response Variations To Erythropoietin Stimulatingsupporting
confidence: 93%
“…HD duration was significantly longer in HCV-positive HD patients than in HCV-negative HD patients, as patients with HCV infection spent a significantly longer time (P≤0.001) on hemodialysis than those without HCV infection. These findings were supported by Saifan et al 20 .…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, it was observed that hemodialysis duration was significantly longer in HCV-positive patients than in HCV-negative patients, as patients with HCV infection spent a significantly longer time [P < 0.001] on hemodialysis than those without HCV infection. These findings were supported by Saifan et al, 2013. We found that HCV hemodialysis patients displayed normal ALT and AST levels in comparison with HCV-negative hemodialysis patients. This agrees with the result of Contreras et al, 2007.…”
Section: Discussionsupporting
confidence: 72%